An investigation of online teaching and lecturers’ online teaching competence in Vietnam: A case study at universities of technology and education - Oanh, Duong Thi Kim; Tuan, Ngo Anh; Duong, Pham Bach; Triet, Nguyen Minh; Phuc, Truong Quang (Journal of Education and e-Learning Research, 2023)
The rapid digital transformation and the widespread influence of the COVID-19 pandemic have impacted higher education in Vietnam. This social setting fosters online teaching and lecturers’ online teaching competencies. The aim of this study is to investigate online teaching competence at two universities of technology and education in Vietnam through a survey. Based on a review of the literature, an online teaching competence scale for lecturers was developed and its validity and reliability were evaluated using exploratory component analysis and Cronbach’s alpha coefficients with data from 311 lecturers at two public universities of technology and education. The online teaching competency scale for lecturers consists of 25 items organized into five component competencies: “Understanding student learning”, “online session administration”, “digital content development and learning facilitation”, “technology” and “online learning outcomes assessment”. With the exception of “technology”, the remaining component competencies were identified as good. Not only online teaching modes but also online teaching activities and productions were also deployed to maintain learning activities especially during the COVID-19 pandemic at two universities. Recommendations for developing lecturers’ online teaching competence were also considered.